Long-COVID neurological symptoms are associated with D-dimer levels in COVID-19 patients (Universa Medicina, 2022)
Background Coronavirus disease 2019 (COVID-19) is a disease designated as a global pandemic by the WHO that can manifest clinically as neurological disorders that can occur in the acute phase or after the acute phase (long COVID-19), such as headache, myalgia, anosmia, and cognitive impairment. These neurological disorders as symptoms of long COVID-19 are presumably caused by hypercoagulable conditions characterized by an increase in D-dimer level. This study aims to determine the correlation of long COVID-19 neurological symptoms with hypercoagulable conditions and the role of D-dimer as a biomarker of long COVID-19 neurological symptoms.MethodsThis was a cross-sectional study involving 31 patients with long COVID-19 symptoms. Admitted long COVID-19 cases with recorded D-dimer levels and definitive outcomes were included consecutively. Long COVID-19 neurological symptoms were collected. D-dimer level was measured using immunofluorescence assay and reported in fibrinogen equivalent units (ìg/mL). The correlation between D-dimer levels and neurological clinical manifestations was assessed by using ordinal regression analysis. The p-value of